IMPLEMENTASI SMART CLASSROOM BERBASIS IOE: STUDI EVALUATIF DENGAN PENDEKATAN PDCA (Plan-Do-Check-Act) DAN MODEL TAM (Technology Acceptance Model): IMPLEMENTATION OF SMART CLASSROOM BASED ON IOE: EVALUATIVE STUDY WITH PDSA APPROACH AND TAM MODEL - Bismar Fadli; Seno Adi Putra; Hanif Fakhrurroja (LPPM Universitas Abdurrab, 2025)
Modern universities are required to transform by embracing digital technologies to support the implementation of the Tri Dharma of Higher Education. This study explores how Indonesian higher education institutions adopt the Smart Classroom concept as part of digital transformation to improve the quality of learning. One of the key initiatives is the creation of interactive and connected learning environments through technology integration. This research proposes a standardized Smart Classroom model based on the Internet of Everything (IoE), utilizing devices such as Interactive Flat Panels, PTZ cameras, smart door locks, Wireless Presentation Displays, and audio systems. The methodology includes literature review, conceptual design, prototype development, and evaluation using the Plan-Do-Check-Act (PDCA) approach. Additionally, the Technology Acceptance Model (TAM) is employed to analyze students’ perceptions and intentions to adopt Smart Classroom technologies. The results show that the application of IoE in Smart Classrooms enhances interaction between lecturers and students, operational efficiency, and provides a more adaptive and comfortable learning experience. The main contribution of this study is the development of a comprehensive implementation guide for IoE-based Smart Classrooms, incorporating technical, managerial, and pedagogical aspects to support the advancement of higher education in the digital era.